Financial implications of trauma patients at a Canadian level 1 trauma center: a retrospective cohort study - Kednapa Thavorn; Peter Glen; Adam M Fontebasso; Sonshire Figueira; Jacinthe Lampron; Maher Matar (Trauma Surgery & Acute Care Open)
Background Trauma is a cause of significant morbidity and mortality globally, and patients with major trauma require specialized settings for multidisciplinary care. We sought to enumerate the variability of costs of caring for patients at a Canadian level 1 trauma center.Methods A retrospective analysis of all adult patients admitted to The Ottawa Hospital trauma service between June 2013 and June 2018 was conducted. Hospital costs and clinical data were collected. Descriptive statistics and multivariable regression analysis using generalized linear model were performed to assess cost variation with patient characteristics. Quintile-based analyses were used to characterize patients in different cost categories. Hospital costs were reported in 2018 Canadian dollars.Results A total of 2381 admissions were identified in the 5-year cohort. The mean age of patients was 50.2 years, the mean Injury Severity Score (ISS) was 18.7, the mean Charlson Comorbidity Index (CCI) score was 0.35, and the median total cost was $10 048.54. ISS and CCI score were associated with higher costs (ISS >15; p<0.0001). The most expensive mechanisms of injury (MOIs) were those involving heavy machinery (median total cost $24 074.38), pedestrians involved in road traffic collisions ($20 965.45), patients in motor vehicle collisions ($17 621.01) and motorcycle collisions ($16 220.89), and acts of self-injury ($13 903.69). Patients who experienced in-hospital adverse events were associated with higher costs (p<0.0001). Our multivariable regression analysis showed variation in costs related to male gender, penetrating/violent MOI, ISS, adverse hospital events, CCI score, urgent admission status, hospital 1-year mortality risk score, and alternate level of care designation (p<0.05). Quintile-based analyses demonstrated clinically significant differences between the highest and lowest cost groups.Discussion Major trauma was associated with high hospital costs. Modifiable and non-modifiable patient factors were shown to correlate with differing total hospital costs. These findings can aid in the development of funding strategies and resource allocation for this complex patient population.Level of evidence Level III evidence for economic and value-based evaluations.